Coated water-retaining slow-release fertilizer and method for preparing the same

CN118496027BActive Publication Date: 2026-10-30HEFEI UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410696670.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-31
Publication Date
2026-10-30
Estimated Expiration
2044-05-31

AI Technical Summary

Technical Problem

针对现有技术的不足,本发明提供了包膜保水缓释肥料及其制备方法,解决了现有肥料利用率低、对环境污染严重,现有保水剂生产成本高、残留物不易降解等技术问题

Benefits of technology

1、本发明的包膜保水缓释肥料制备工艺简单,制备全程未使用有机溶剂、制备过程绿色友好,制备的包膜保水缓释肥料将肥料与保水剂相结合,具备良好的保水性能和缓释性能,提高肥料养分利用率的同时具备环境效应和经济效应。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118496027B_ABST
    Figure CN118496027B_ABST
Patent Text Reader

Abstract

The application provides an environment-friendly coated water-retaining slow-release fertilizer, and relates to the technical field of agricultural slow-release fertilizer.The coated water-retaining slow-release fertilizer comprises, from inside to outside, an inner layer of fertilizer core particles, an intermediate layer of a binder and an outer layer of a high-molecular coating material.The inner layer of fertilizer core particles is urea particles or nitrogen-phosphorus-potassium compound fertilizer particles.The intermediate layer of the binder is cactus mucilage solid.The outer layer of the high-molecular coating material is inorganic modified polyvinyl alcohol coating liquid solid.The preparation method specifically comprises the following steps: S1.cactus mucilage preparation;S2.inorganic modified polyvinyl alcohol coating liquid preparation;and S3.coating treatment.The coated water-retaining slow-release fertilizer has a simple preparation process, does not use organic solvents in the whole preparation process, and has a green and friendly preparation process.The prepared coated water-retaining slow-release fertilizer combines the fertilizer and the water-retaining agent, has good water-retaining performance and slow-release performance, improves the fertilizer nutrient utilization rate, and has environmental effects and economic effects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the technical field of agricultural slow-release fertilizers, specifically to a coated water-retaining slow-release fertilizer and its preparation method. Background Technology

[0002] Dryland accounts for over 50% of my country's total land area, hindering sustainable agricultural development. Prolonged soil water shortages inhibit plant organ formation, root absorption of minerals, and the transport of organic nutrients. Therefore, to fully utilize limited rainfall resources and promote high- and stable agricultural yields, it is crucial to vigorously develop water-saving and water-conserving technologies for dryland farmland. Applying water-retaining agents is an effective method to alleviate drought; these agents can repeatedly absorb and slowly release water, reducing leaching loss of soluble nutrients and improving soil structure. However, existing water-retaining agents lack fertilizer nutrients, and their high production costs and persistent residues limit their widespread use.

[0003] Fertilizers play a vital role in increasing crop yields; however, conventional fertilizers suffer from low utilization rates. Currently, nitrogen fertilizer utilization is only around 30%, phosphorus fertilizer around 15%, and potassium fertilizer around 45%. This significant fertilizer loss not only causes substantial economic losses but also severely pollutes the environment. Furthermore, applying water-retaining agents and fertilizers separately is time-consuming and labor-intensive, hindering the maximization of water and fertilizer efficiency.

[0004] Based on the above, the present invention provides a coated water-retaining slow-release fertilizer and its preparation method, which combines a water-retaining agent with fertilizer to prepare a coated water-retaining slow-release fertilizer with advantages such as high water retention, environmental friendliness, and high fertilizer utilization rate. Summary of the Invention

[0005] (a) Technical problems to be solved To address the shortcomings of existing technologies, this invention provides a coated water-retaining slow-release fertilizer and its preparation method, which solves the technical problems of low utilization rate of existing fertilizers, serious environmental pollution, high production cost of existing water-retaining agents, and difficulty in degrading residues.

[0006] (II) Technical Solution To achieve the above objectives, the present invention provides the following technical solution: The coated water-retaining slow-release fertilizer consists of, from the inside out, an inner layer of fertilizer core granules, a middle layer of binder, and an outer layer of polymer coating material. The inner fertilizer core particles are urea particles or nitrogen-phosphorus-potassium compound fertilizer particles. The intermediate layer adhesive is a solid cactus mucus. The outer polymer coating material is an inorganic modified polyvinyl alcohol coating liquid solid.

[0007] The preparation method of coated water-retaining slow-release fertilizer specifically includes the following steps: S1. Preparation of cactus mucus: After cutting the cactus into pieces, put them into a grinder, add water and grind them thoroughly to obtain a cactus-water mixture. Then, centrifuge the cactus-water mixture to obtain a cactus aqueous solution. Finally, evaporate the cactus aqueous solution to obtain cactus mucus. S2. Preparation of inorganically modified polyvinyl alcohol coating solution: Polyvinyl alcohol was dissolved in water under heating and stirring conditions to obtain a homogeneous polyvinyl alcohol solution; biochar, nano-silica, or bentonite were added to the polyvinyl alcohol solution, and the mixture was heated and stirred, then heated and ultrasonically dispersed; glutaraldehyde was added to the above solution, and dilute hydrochloric acid was added to adjust the pH of the solution, and the mixture was heated and stirred to react; the solution was allowed to stand to remove bubbles to obtain an inorganically modified polyvinyl alcohol coating solution. S3. Coating treatment: Preheat the fertilizer core granules; repeatedly and evenly spray cactus mucus onto the surface of the fertilizer core granules; then evenly spray inorganic modified polyvinyl alcohol coating liquid onto the fertilizer core granules with cactus mucus on the surface; dry the coating material to obtain coated water-retaining slow-release fertilizer.

[0008] Preferably, the mass ratio of the cactus block to water in step S1 is 1:1 to 1:2.

[0009] Preferably, the centrifugation time of the cactus-water mixture in step S1 is ≥10 min.

[0010] Preferably, the cactus solution in step S1 is evaporated to 1 / 3 to 1 / 2 of its initial volume to obtain cactus mucus.

[0011] Preferably, in step S2, relative to 100 parts by weight of water, the amount of polyvinyl alcohol is 5-8 parts, the amount of biochar / nano silica / bentonite is 0.5-2 parts, and the amount of glutaraldehyde is 0.5-2 parts.

[0012] Preferably, in step S2, the heating temperature for dissolving the polyvinyl alcohol in water is 80~100 ℃; after adding biochar, nano silica, or bentonite, the heating and stirring temperature is 30~80 ℃, the stirring time is ≥30 min, the ultrasonic heating temperature is 30~60 ℃, and the ultrasonic dispersion treatment time is ≥10 min; the concentration of the dilute hydrochloric acid is 0.1~0.5 mol / L, the pH of the solution is adjusted to 3~4, the heating temperature is 50~90 ℃, and the stirring reaction time is ≥30 min; the solution after pH adjustment is allowed to stand for ≥2 h.

[0013] Preferably, in step S3, the instrument used for coating is a rotary drum coating machine, wherein the fan temperature of the rotary drum coating machine is 50~100 ℃ and the drum rotation speed is 20~60 r / min.

[0014] Preferably, in step S3, the radius of the fertilizer core particles is ≥0.2 cm, the preheating time is ≥5 min, and the drying time of the obtained coating material in the rotary drum coating machine is ≥20 min.

[0015] Preferably, in step S3, the mass ratio of the cactus mucus to the inorganic modified polyvinyl alcohol coating solution is 10-20%, and the mass ratio of the sum of the solids of the cactus mucus and the solids of the inorganic modified polyvinyl alcohol coating solution in the prepared coated water-retaining slow-release fertilizer to the mass of the fertilizer core particles is 2-10%.

[0016] (III) Beneficial Effects This invention provides a coated, water-retaining, slow-release fertilizer and its preparation method. Compared with the prior art, it has the following advantages: 1. The preparation process of the coated water-retaining slow-release fertilizer of the present invention is simple, no organic solvents are used in the entire preparation process, and the preparation process is green and friendly. The prepared coated water-retaining slow-release fertilizer combines fertilizer with water-retaining agent, which has good water retention and slow-release performance, improves fertilizer nutrient utilization rate, and has environmental and economic benefits.

[0017] 2. The coated water-retaining slow-release fertilizer of the present invention has excellent water retention performance. When the application rate of the coated water-retaining slow-release fertilizer of the present invention is 0.5%, it increases the maximum water holding capacity of the soil by 1.5~5.04%; compared with the soil without the application of the coated water-retaining slow-release fertilizer of the present invention, the average soil moisture evaporation rate is reduced by 8.02~18.20% when the application rate of the coated water-retaining slow-release fertilizer of the present invention is 0.5%, 1%, and 2%.

[0018] 3. The coated water-retaining slow-release fertilizer of the present invention has excellent slow-release performance. The time required for the nutrient release of the coated water-retaining slow-release fertilizer of the present invention to reach 90% is 26-30 days, while the uncoated urea granules release more than 99% of the fertilizer nutrients in only 5 days.

[0019] 4. The coated water-retaining slow-release fertilizer of the present invention has high strength and is easy to transport. The compressive strength of the coated water-retaining slow-release fertilizer of the present invention is 23~26.5 N, which far exceeds the 11.5 N of uncoated urea granules.

[0020] 5. The inorganic modified polyvinyl alcohol coating solution used in this invention is environmentally friendly and biodegradable, and its degradation products are harmless to the soil; biochar is a substance with high aromatic stability and porous structure produced by thermochemical treatment of organic materials under anaerobic conditions. Its raw materials are renewable and biodegradable. Biochar can improve soil properties, such as enhancing water retention capacity and increasing soil nutrient supply; nano-silica has the advantages of strong adsorption capacity, non-toxicity, odorlessness, and high stability. Silicon has been listed by the international soil community as the fourth largest element after nitrogen, phosphorus, and potassium; bentonite is a natural mineral material, a layered silicate, with advantages such as high surface area and good stability, and is generally used as a soil additive.

[0021] 6. The intermediate layer binder used in this invention, cactus mucus, is a natural viscous biopolymer. Its main monomers are d-glucose, d-galactose, l-arabinose, d-xylose, l-rhamnose, d-galacturonic acid, and glucuronic acid, which are non-toxic and harmless. Attached Figure Description

[0022] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0023] Figure 1 The graph shows the change in water content of each coating in Examples 1-3 of the present invention over time. In the graph, PVA-Bi is the biochar-modified polyvinyl alcohol coating of Example 1, PVA-Si is the nano-silica-modified polyvinyl alcohol coating of Example 2, and PVA-Be is the bentonite-modified polyvinyl alcohol coating of Example 3. Figure 2 The figures show the contact angles of the coatings in Examples 1-3 of this invention. In the figures, PVA-Bi is the biochar-modified polyvinyl alcohol coating of Example 1, PVA-Si is the nano-silica-modified polyvinyl alcohol coating of Example 2, and PVA-Be is the bentonite-modified polyvinyl alcohol coating of Example 3. Figure 3 (a) is Example 1. Figure 3 (b) is Example 2. Figure 3 (c) is a soil moisture evaporation rate-time curve of the coated water-retaining slow-release fertilizer of Example 3; Figure 4 The diagram shows the maximum soil water holding capacity of the coated water-retaining slow-release fertilizers of Examples 1-3 and Comparative Example 1 of this invention. Figure 5 The fertilizer nutrient release behavior of Examples 1-3 and Comparative Example 1 of this invention; Figure 6 This is the FTIR spectrum of the cactus mucus, the intermediate layer adhesive, in Example 1 of the present invention. Detailed Implementation

[0024] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention are described clearly and completely. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0025] This application provides a coated, water-retaining, slow-release fertilizer and its preparation method, which solves the technical problems of low utilization rate and serious environmental pollution of existing fertilizers, as well as high production cost and poor water retention of existing water-retaining agents.

[0026] To better understand the above technical solutions, the following will provide a detailed explanation of the technical solutions in conjunction with the accompanying drawings and specific implementation methods.

[0027] The specifications and manufacturers of some of the raw materials used in this invention are shown in the table below.

[0028] Example 1: The coated water-retaining slow-release fertilizer consists of, from the inside out, urea granules, cactus mucilage solids, and biochar-modified polyvinyl alcohol coated liquid solids.

[0029] The preparation method of coated water-retaining slow-release fertilizer includes the following steps: S1. Preparation of cactus mucus: Take a cactus leaf and cut it into 2×2 cm pieces. 2 The cubes were mixed with water at a mass ratio of 1:1.5 at room temperature and then crushed in a grinder to obtain a cactus water mixture. The cactus water mixture was then centrifuged for 15 minutes, and the upper layer solution was taken as the cactus aqueous solution. Finally, the cactus aqueous solution was rotary evaporated to 1 / 2 of the initial volume to obtain cactus mucus. S2. Preparation of biochar-modified polyvinyl alcohol coating solution: 8 g of polyvinyl alcohol was added to 92 g of water and stirred in a 90°C water bath for 0.5 h to obtain a homogeneous polyvinyl alcohol solution with a mass fraction of 8 wt%. 1 g of biochar was added to the obtained polyvinyl alcohol solution, and the mixture was heated and stirred at 70°C for 1 h, followed by ultrasonic dispersion at 40°C for 20 min. 0.8 mL of glutaraldehyde was added to the obtained polyvinyl alcohol solution with added biochar, and then 0.1 mol / L dilute hydrochloric acid solution was added to adjust the pH of the solution to 3-4. The mixture was stirred at 70°C for another 0.5 h. The solution was allowed to stand for 2 h to remove air bubbles, resulting in a biochar-modified polyvinyl alcohol coating solution. S3. Coating treatment: Turn on the rotary drum coating machine, set the fan temperature to 70℃ and the drum speed to 40 r / min; take urea granules with a radius of 3~4 mm and preheat them in the rotary drum coating machine for 10 min; repeatedly and evenly spray cactus mucus onto the surface of the fertilizer core granules; then evenly spray biochar-modified polyvinyl alcohol coating liquid onto the urea granules with cactus mucus on the surface; the mass ratio of cactus mucus to biochar-modified polyvinyl alcohol coating liquid is 15%; finally, dry the prepared coated urea granules in the rotary drum coating machine for 60 min to obtain coated water-retaining slow-release fertilizer, the mass ratio of the sum of the solids of cactus mucus and the solids of biochar-modified polyvinyl alcohol coating liquid to the mass of urea granules is 6%.

[0030] The prepared coated water-retaining slow-release fertilizer was characterized by its soil maximum water holding capacity, soil moisture evaporation rate, compressive strength, and nutrient release performance. The specific methods are as follows: Maximum soil water holding capacity: determined using the soil column method. A layer of filter paper was first laid at the bottom of a polyvinyl chloride (PVC) pipe (8 cm in diameter, 30 cm high), followed by 100 g of air-dried soil (passed through a 65-mesh sieve). Coated water-retaining slow-release fertilizer granules were mixed evenly with 200 g of air-dried soil and added to the PVC pipe (fertilizer granule to air-dried soil mass ratios were 0%, 0.5%, 1%, and 2%). Another 100 g of air-dried soil was added to the top of the PVC pipe to form a soil column, which was then weighed (W1). After the soil column was assembled, tap water was slowly poured into it from the top of the PVC pipe, allowing water to penetrate the entire column until water seeped out from the bottom. The column was allowed to stand, and its mass was measured periodically until it reached a constant value. The total mass was then recorded (W2). Maximum soil water holding capacity (W) max The calculation formula for is as follows.

[0031] Soil moisture evaporation rate: Mix the coated water-retaining slow-release fertilizer granules and 200 g of air-dried soil evenly into a beaker (the mass ratio of fertilizer granules to air-dried soil is 0%, 0.5%, 1%, and 2%), add 200 g of water, and weigh (m). i Periodically measure the total mass of the beaker (m). n), calculate the soil moisture evaporation rate according to the following formula ( η ).

[0032] Compressive strength: The compressive strength of the coated water-retaining slow-release fertilizer granules was determined using a granule strength tester. The test sample was placed in the center of the sample pan, and the upper handwheel was rotated clockwise to move the force lever down. The data on the display increased with the increase of the test force. When the sample granules broke, the maximum force value was locked, and the maximum strength value was displayed digitally.

[0033] Fertilizer nutrient slow-release performance: First, air-dried soil was sieved through a 65-mesh sieve. Then, 50 grams of dry soil were placed in a 100 mL plastic cup. Next, 0.5 grams of coated water-retaining slow-release fertilizer granules were added to a non-woven fabric bag, which was then placed in the cup. 10 mL of deionized water was added to the cup to maintain the soil moisture content at ~20 wt%. Throughout the experiment, the soil moisture content in the cup was maintained at 20 wt%, and weighed every 3 days, with water added as needed. At 6, 12, 24, 120, 240, 480, and 720 hours, the coated water-retaining slow-release fertilizer granules in the non-woven fabric bag were removed, dried, ground into powder, dissolved in deionized water, and the remaining nitrogen content was measured.

[0034] In this embodiment, the soil moisture evaporation rates at mass ratios of 0%, 0.5%, 1%, and 2% to air-dried soil are as follows: Figure 3 As shown in Figure a), the soil moisture evaporation rate after 30 days was 98.62% when the application rate was 0%, while the evaporation rates for application rates of 0.5%, 1%, and 2% were 88.01%, 85.45%, and 80.82%, respectively, representing an average reduction of 13.86%. The maximum water holding capacity of the soil at application rates of 0%, 0.5%, 1%, and 2% of the air-dried soil in this example is shown below. Figure 4 As shown, when the application rate in this embodiment is 0%, 0.5%, 1.0%, and 2.0%, the maximum soil water holding capacity is 32.25%, 36.11%, 40.34%, and 43.01%, respectively. It can be seen that the maximum soil water holding capacity continuously increases with the increase in the application rate, indicating that the application of this embodiment can improve the maximum soil water holding capacity. Furthermore, compared with the uncoated fertilizer granules of Comparative Example 1, it is also evident that this embodiment can improve the maximum soil water holding capacity. In summary, the coated water-retaining slow-release fertilizer prepared in this embodiment has good water retention performance.

[0035] The nutrient slow-release behavior in this embodiment is as follows: Figure 5 As shown, in this embodiment, the time required for the fertilizer nutrient release to reach 90% is 28 days, and the total nutrient release period exceeds 30 days. In contrast, Comparative Example 1 released more than 99% of the fertilizer nutrients in just 5 days, indicating that this embodiment has the effect of slow-release fertilizer nutrients.

[0036] The compressive strength values ​​of this embodiment are shown in Table 1. The compressive strength of this embodiment is 25 N, which is much higher than that of Comparative Example 1 (11.5 N), indicating that the coated water-retaining fertilizer prepared in this embodiment has good compressive strength.

[0037] The FTIR spectrum of the cactus mucus in this embodiment is as follows: Figure 6 As shown, with 3383 cm -1 The broad bandwidth centered on this point represents the hydrogen bonds formed between the -OH groups of carbohydrates and acids in the sample, at 2935 cm⁻¹. -1 The absorption peak at this point corresponds to the stretching vibrations of -CH2 and -CH3, and is present in the pyranose and furanose conformations of galactose, arabinose, and xylose; these are the most common monosaccharides in cactus mucus. 1611 cm⁻¹ -1 and 1416 cm -1 The absorption peaks observed at these locations are the COO and O of carboxylic acids, respectively. - Tensile vibration and asymmetric vibration belong to hyaluronic acid, which is usually found in mucus. The interaction between the carboxylic acid group of uronic acid and water and cations can increase the viscosity of mucus. Therefore, in the embodiments of the present invention, using cactus mucus as an intermediate adhesive layer can effectively improve the bonding strength between the outer and inner layers.

[0038] Example 2: The coated water-retaining slow-release fertilizer consists of, from the inside out, urea granules, cactus mucilage solids, and nano-silica modified polyvinyl alcohol coated liquid solids.

[0039] The preparation method of coated water-retaining slow-release fertilizer includes the following steps: S1. Preparation of cactus mucus: Take a cactus leaf and cut it into 2×2 cm pieces. 2 The cubes were mixed with water at a mass ratio of 1:1 at room temperature and then crushed in a grinder to obtain a cactus water mixture. The cactus water mixture was then centrifuged for 15 minutes, and the upper layer solution was taken as the cactus aqueous solution. Finally, the cactus aqueous solution was rotary evaporated to 1 / 3 of the initial volume to obtain cactus mucus. S2. Preparation of polyvinyl alcohol coating solution modified with nano-silica: 8 g of polyvinyl alcohol was added to 92 g of water and stirred in a 90°C water bath for 0.5 h to obtain a homogeneous polyvinyl alcohol solution with a mass fraction of 8 wt%. 1 g of nano-silica was added to the obtained polyvinyl alcohol solution, and the mixture was heated and stirred at 70°C for 1 h, followed by ultrasonic dispersion at 40°C for 20 min. 0.8 mL of glutaraldehyde was added to the obtained polyvinyl alcohol solution with added nano-silica, and then 0.1 mol / L dilute hydrochloric acid solution was added to adjust the pH of the solution to 3-4. The mixture was stirred at 70°C for another 0.5 h. The solution was allowed to stand for 2 h to remove air bubbles, resulting in a polyvinyl alcohol coating solution modified with nano-silica. S3. Coating treatment: Turn on the rotary drum coating machine, set the fan temperature to 50℃ and the drum speed to 60 r / min; take urea granules with a radius of 3~4 mm and preheat them in the rotary drum coating machine for 10 min; repeatedly and evenly spray cactus mucus onto the surface of the fertilizer core granules; then evenly spray the nano-silica modified polyvinyl alcohol coating liquid onto the urea granules with cactus mucus on the surface; the mass ratio of cactus mucus to nano-silica modified polyvinyl alcohol coating liquid is 10%; finally, dry the prepared coated urea granules in the rotary drum coating machine for 60 min to obtain coated water-retaining slow-release fertilizer, the mass ratio of the sum of the solids of cactus mucus and the solids of nano-silica modified polyvinyl alcohol coating liquid to the mass of urea granules is 2%.

[0040] In this embodiment, the soil moisture evaporation rates at ratios of 0%, 0.5%, 1%, and 2% to air-dried soil mass are as follows: Figure 3 As shown in b), the soil moisture evaporation rate after 30 days was 98.62% when the application rate was 0%, while the evaporation rates were 95.31%, 90.25%, and 86.29% when the application rates were 0.5%, 1%, and 2%, respectively, representing an average reduction of 8.02%. The maximum water holding capacity of the soil at application rates of 0%, 0.5%, 1%, and 2% of the air-dried soil mass in this embodiment is shown in the figure. Figure 4 As shown, when the application rate in this embodiment is 0%, 0.5%, 1.0%, and 2.0%, the maximum soil water holding capacity is 32.25%, 33.75%, 37.88%, and 40.31%, respectively. It can be seen that the maximum soil water holding capacity continuously increases with the increase in the application rate, indicating that the application of this embodiment can improve the maximum soil water holding capacity. Furthermore, compared with the uncoated fertilizer granules of Comparative Example 1, this embodiment also shows that it can improve the maximum soil water holding capacity. In summary, the coated water-retaining slow-release fertilizer prepared in this embodiment has good water retention performance.

[0041] The nutrient slow-release behavior in this embodiment is as follows: Figure 5As shown, the time required for the fertilizer nutrient release in this embodiment to reach 90% is 26 days, and the total nutrient release period exceeds 30 days. In contrast, Comparative Example 1 released more than 99% of the fertilizer nutrients in just 5 days, indicating that this embodiment has the effect of slow-release fertilizer nutrients.

[0042] The compressive strength values ​​of this embodiment are shown in Table 1. The compressive strength of this embodiment is 26.5 N, which is much higher than that of Comparative Example 1 (11.5 N), indicating that this embodiment has better compressive strength.

[0043] Example 3: The coated water-retaining slow-release fertilizer consists of, from the inside out, nitrogen, phosphorus, and potassium compound fertilizer granules, cactus mucilage solids, and bentonite polyvinyl alcohol coating liquid solids.

[0044] The preparation method of coated water-retaining slow-release fertilizer includes the following steps: S1. Preparation of cactus mucus: Take a cactus leaf and cut it into 2×2 cm pieces. 2 The cubes were mixed with water at a mass ratio of 1:2 at room temperature and then crushed in a grinder to obtain a cactus water mixture. The cactus water mixture was then centrifuged for 15 minutes, and the upper layer solution was taken as the cactus aqueous solution. Finally, the cactus aqueous solution was rotary evaporated to 1 / 3 of the initial volume to obtain cactus mucus. S2. Preparation of polyvinyl alcohol coating solution modified with nano-silica: 8 g of polyvinyl alcohol was added to 92 g of water and stirred in a 90°C water bath for 0.5 h to obtain a homogeneous polyvinyl alcohol solution with a mass fraction of 8 wt%. 1 g of bentonite was added to the obtained polyvinyl alcohol solution, and the mixture was heated and stirred at 70°C for 1 h, followed by ultrasonic dispersion at 40°C for 20 min. 0.8 mL of glutaraldehyde was added to the obtained polyvinyl alcohol solution with added bentonite, and then 0.1 mol / L dilute hydrochloric acid solution was added to adjust the pH of the solution to 3-4. The mixture was stirred at 70°C for another 0.5 h. The solution was allowed to stand for 2 h to remove air bubbles, resulting in a bentonite-modified polyvinyl alcohol coating solution. S3. Coating treatment: Turn on the rotary drum coating machine, set the fan temperature to 100℃ and the drum speed to 20 r / min; take NPK compound fertilizer granules with a radius of 3~4 mm and preheat them in the rotary drum coating machine for 10 min; repeatedly and evenly spray cactus mucus onto the surface of the fertilizer core granules; then evenly spray bentonite-modified polyvinyl alcohol coating liquid onto the NPK compound fertilizer granules with cactus mucus on the surface; the mass ratio of cactus mucus to bentonite-modified polyvinyl alcohol coating liquid is 20%; finally, dry the prepared coated NPK compound fertilizer granules in the rotary drum coating machine for 60 min to obtain coated water-retaining slow-release fertilizer, the mass ratio of the sum of the solids of cactus mucus and the solids of bentonite-modified polyvinyl alcohol coating liquid to the mass of NPK compound fertilizer granules is 10%.

[0045] In this embodiment, the soil moisture evaporation rates at ratios of 0%, 0.5%, 1%, and 2% to air-dried soil mass are as follows: Figure 3 As shown in Figure c), the soil moisture evaporation rate after 30 days was 98.62% when the application rate was 0%, while the evaporation rates were 83.11%, 81.05%, and 77.09% when the application rates were 0.5%, 1%, and 2%, respectively, representing an average reduction of 18.20%. The maximum water holding capacity of the soil at application rates of 0%, 0.5%, 1%, and 2% of the air-dried soil mass in this example is shown below. Figure 4 As shown, when the application rate in this embodiment is 0%, 0.5%, 1.0%, and 2.0%, the maximum soil water holding capacity is 32.25%, 37.29%, 45.35%, and 50.25%, respectively. It can be seen that the maximum soil water holding capacity continuously increases with the increase in the application rate, indicating that the application of this embodiment can improve the maximum soil water holding capacity. Furthermore, compared with the uncoated fertilizer granules of Comparative Example 1, it is also evident that this embodiment can improve the maximum soil water holding capacity. In summary, the coated water-retaining slow-release fertilizer prepared in this embodiment has good water retention performance.

[0046] The nutrient slow-release behavior in this embodiment is as follows: Figure 5 As shown, the time required for the fertilizer nutrient release in this embodiment to reach 90% is 30 days, while Comparative Example 1 released more than 99% of the fertilizer nutrients in just 5 days, indicating that this embodiment has the effect of slow-release fertilizer nutrients.

[0047] The compressive strength values ​​of this embodiment are shown in Table 1. The compressive strength of this embodiment is 23 N, which is much higher than that of Comparative Example 1 (11.5 N), indicating that this embodiment has better compressive strength.

[0048] The difference between Comparative Example 1 and Example 2 is as follows: This comparative example uses uncoated urea particles with a diameter of 3-4 mm.

[0049] The compressive strength of this comparative example is shown in Table 1, which is 11.5 N, indicating that the compressive strength of the urea particles in this comparative example is significantly lower than that of Examples 1-3.

[0050] Comparative Example 2 differs from Example 2 in that: In this comparison, the polyvinyl alcohol coating layer was not modified using inorganic materials.

[0051] The compressive strength values ​​of this comparative example are shown in Table 1, which is 17.5 N. This indicates that compared with Examples 1-3, the compressive strength of the coated water-retaining slow-release fertilizer will decrease after using pure polyvinyl alcohol coating material.

[0052] Comparative Example 3 differs from Example 2 in that: This comparative example uses diatomaceous earth to modify polyvinyl alcohol.

[0053] The compressive strength values ​​of this comparative example are shown in Table 1, which is 20.5 N. This indicates that the compressive strength of the coated water-retaining slow-release fertilizer prepared by modifying polyvinyl alcohol with diatomaceous earth is not as good as that prepared by modifying polyvinyl alcohol with the materials of Examples 1-3.

[0054] Comparative Example 4 differs from Example 2 in that: This comparative example uses polylactic acid instead of polyvinyl alcohol as the outer coating solution.

[0055] The compressive strength values ​​of this comparative example are shown in Table 1, which is 19.5 N. This indicates that using polylactic acid as a coating material does not have a better effect on improving the compressive strength of the slow-release fertilizer than using polyvinyl alcohol as a coating material.

[0056] Comparative Example 5 differs from Example 2 in that: This comparative example uses Bletilla striata gum as the intermediate layer adhesive.

[0057] The compressive strength of this comparative example is shown in Table 1, which is 20.0 N. The bonding performance test data is shown in Table 2, which shows a bonding strength of 3.5 MPa. This indicates that although Bletilla striata gum also has good bonding performance, its bonding strength is not as good as that of cactus mucilage. As a result, the compressive strength of the prepared coated water-retaining slow-release fertilizer is not as high as that of the coated water-retaining slow-release fertilizer prepared using cactus mucilage as an intermediate layer binder.

[0058] Comparative Example 6 differs from Example 2 in that: This comparative example does not add an intermediate layer binder. The coated water-retaining slow-release fertilizer consists of urea granules and nano-silica modified polyvinyl alcohol coated liquid solids from the inside out.

[0059] The compressive strength of this comparative example is shown in Table 1, which is 15.0 N. The bonding performance test data is shown in Table 2, with a bonding strength of 2.0 MPa. Furthermore, during the spraying of the polyvinyl alcohol coating solution, some of the coating solution dissolved the fertilizer core particles, resulting in large-area unevenness and blistering after film formation. This demonstrates the importance of the intermediate layer binder for the water-retaining slow-release fertilizer of this invention. As an intermediate layer, it can improve the technical defect of easy dissolution when the polyvinyl alcohol coating solution is directly sprayed onto the surface of fertilizer particles, and can significantly improve the compressive strength and water retention properties of the coated water-retaining slow-release fertilizer.

[0060] Performance testing 1. The moisture content and contact angle properties of the inorganic-modified polyvinyl alcohol coatings prepared in Examples 1-3 were characterized, and the characterization results are as follows: Figure 1 , Figure 2 As shown.

[0061] Depend on Figure 1 It can be seen that the water content of all three membranes gradually increases over time until they reach an equilibrium state. The PVA-Be membrane has the highest water content, reaching 552.98% within 30 minutes. This is because bentonite has good hydrophilicity and can absorb 8 to 20 times its own volume of water. The PVA-Si membrane has the lowest water content, reaching 245.55% within 45 minutes. This is because the addition of nano-SiO2 can improve the water resistance of the composite membrane. Biochar can also improve the hydrophilicity of the membrane, but its hydrophilicity is not as good as that of bentonite. Therefore, the water content of the PVA-Bi membrane reaches 435.26% within 30 minutes.

[0062] The contact angle reflects the wettability and hydrophilicity of a material surface. Generally, the smaller the contact angle, the better the hydrophilicity of the material. This is due to the formation of hydrogen bonds between water molecules and the material. Figure 2 It can be seen that the PVA-Si film has the largest contact angle, exceeding 90°. o Exhibiting hydrophobicity, the contact angles of the PVA-Bi and PVA-Be films are 72.6° and 72.6°, respectively. o 61.3 o The membrane exhibits hydrophilicity, and these results are consistent with the membrane's water content results.

[0063] 2. Compressive strength test Samples of the fertilizers prepared by Examples 1-3 and Comparative Examples 1-6 were taken and the following performance tests were performed on the samples. The test results are shown in Table 1.

[0064] Table 1 - Compressive strength values ​​of the embodiments and comparative examples of the present invention 3. Adhesion performance testing Samples of fertilizers prepared by Examples 1-3 and Comparative Examples 5-6 were taken and the following performance tests were performed on the samples. Among them, the bonding strength refers to the bonding strength between the outer layer, the middle layer as a whole and the inner fertilizer core. The test results are shown in Table 2.

[0065] Table 2 - Adhesion test data of the coated slow-release fertilizer layer in the embodiments and comparative examples of the present invention In summary, compared with existing technologies, it has the following beneficial effects: 1. The preparation process of the coated water-retaining slow-release fertilizer of the present invention is simple, no organic solvents are used in the entire preparation process, the preparation process is green and friendly, the prepared coated water-retaining slow-release fertilizer combines fertilizer with water-retaining agent, has good water retention and slow-release performance, improves fertilizer nutrient utilization rate while having environmental and economic benefits.

[0066] 2. The coated water-retaining slow-release fertilizer of the present invention has excellent water retention performance. When the application rate of the coated water-retaining slow-release fertilizer of the present invention is 0.5%, it increases the maximum water holding capacity of the soil by 1.5~5.04%; compared with the soil without the application of the coated water-retaining slow-release fertilizer of the present invention, the average soil moisture evaporation rate is reduced by 8.02~18.20% when the application rate of the coated water-retaining slow-release fertilizer of the present invention is 0.5%, 1%, and 2%.

[0067] 3. The coated water-retaining slow-release fertilizer of the present invention has excellent slow-release performance. The time required for the nutrient release of the coated water-retaining slow-release fertilizer of the present invention to reach 90% is 26-30 days, while the uncoated urea granules release more than 99% of the fertilizer nutrients in only 5 days.

[0068] 4. The coated water-retaining slow-release fertilizer of the present invention has high strength and is easy to transport. The compressive strength of the coated water-retaining slow-release fertilizer of the present invention is 23~26.5 N, which far exceeds the 11.5 N of uncoated urea granules.

[0069] 5. The inorganic modified polyvinyl alcohol coating solution used in this invention is environmentally friendly and biodegradable, and its degradation products are harmless to the soil; biochar is a substance with high aromatic stability and porous structure produced by thermochemical treatment of organic materials under anaerobic conditions. Its raw materials are renewable and biodegradable. Biochar can improve soil properties, such as enhancing water retention capacity and increasing soil nutrient supply; nano-silica has the advantages of strong adsorption capacity, non-toxicity, odorlessness, and high stability. Silicon has been listed by the international soil community as the fourth largest element after nitrogen, phosphorus, and potassium; bentonite is a natural mineral material, a layered silicate, with advantages such as high surface area and good stability, and is generally used as a soil additive.

[0070] 6. The intermediate layer binder used in this invention, cactus mucus, is a natural viscous biopolymer. Its main monomers are d-glucose, d-galactose, l-arabinose, d-xylose, l-rhamnose, d-galacturonic acid, and glucuronic acid, which are non-toxic and harmless.

[0071] 7. The intermediate cactus mucilage solid material and the outer inorganic modified polyvinyl alcohol coating solid material of the present invention have a synergistic effect. No matter whether the intermediate layer is deleted or replaced with other plant glues, or the outer coating material is replaced, the technical effect of the materials used in the technical solution of the present invention cannot be achieved.

[0072] It should be noted that, in this document, relational terms such as "first" and "second" are used only to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Without further limitations, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes said element.

[0073] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A coated, water-retaining, slow-release fertilizer, characterized in that, From the inside out, the layers are: inner fertilizer core granules, middle binder, and outer polymer coating material. The inner fertilizer core particles are urea particles or nitrogen-phosphorus-potassium compound fertilizer particles. The intermediate layer adhesive is cactus sap; The outer polymer coating material is an inorganic modified polyvinyl alcohol coating solution; The fertilizer preparation method specifically includes the following steps: S1. Preparation of cactus mucus: After cutting the cactus into pieces, put them into a grinder, add water and grind them thoroughly to obtain a cactus-water mixture. Then, centrifuge the cactus-water mixture to obtain a cactus aqueous solution. Finally, evaporate the cactus aqueous solution to obtain cactus mucus. S2. Preparation of inorganically modified polyvinyl alcohol coating solution: Polyvinyl alcohol was dissolved in water under heating and stirring conditions to obtain a homogeneous polyvinyl alcohol solution. One of biochar, nano-silica, or bentonite was added to the polyvinyl alcohol solution, and the mixture was heated and stirred before being ultrasonically dispersed. Glutaraldehyde was added to the above solution, and dilute hydrochloric acid was added to adjust the pH of the solution. The mixture was then heated and stirred to react. The solution was allowed to stand to remove air bubbles to obtain an inorganically modified polyvinyl alcohol coating solution. S3. Coating treatment: Preheat the fertilizer core granules; repeatedly and evenly spray cactus mucus onto the surface of the fertilizer core granules; then evenly spray inorganic modified polyvinyl alcohol coating liquid onto the fertilizer core granules with cactus mucus on the surface; dry the coated fertilizer granules to obtain coated water-retaining slow-release fertilizer.

2. The coated water-retaining slow-release fertilizer as described in claim 1, characterized in that, The mass ratio of cactus chunks to water in step S1 of the fertilizer preparation method is 1:1 to 1:

2.

3. The coated water-retaining slow-release fertilizer as described in claim 1, characterized in that, The centrifugation time of the cactus-water mixture in step S1 of the fertilizer preparation method is ≥10 min.

4. The coated water-retaining slow-release fertilizer as described in claim 1, characterized in that, In step S1 of the fertilizer preparation method, the cactus aqueous solution is evaporated to 1 / 3 to 1 / 2 of its initial volume to obtain cactus mucus.

5. The coated water-retaining slow-release fertilizer as described in claim 1, characterized in that, In step S2 of the fertilizer preparation method, relative to 100 parts by weight of water, the amount of polyvinyl alcohol is 5-8 parts, the amount of biochar, nano silica or bentonite is 0.5-2 parts, and the amount of glutaraldehyde is 0.5-2 parts.

6. The coated water-retaining slow-release fertilizer as described in claim 1, characterized in that, In step S2 of the fertilizer preparation method, the heating temperature for dissolving polyvinyl alcohol in water is 80~100 ℃; after adding biochar, nano silica, or bentonite, the heating and stirring temperature is 30~80 ℃, the stirring time is ≥30 min, the ultrasonic heating temperature is 30~60 ℃, and the ultrasonic dispersion treatment time is ≥10 min; the concentration of dilute hydrochloric acid is 0.1~0.5 mol / L, the pH of the solution is adjusted to 3~4, the heating temperature is 50~90 ℃, and the stirring reaction time is ≥30 min; the solution after pH adjustment is allowed to stand for ≥2 h.

7. The coated water-retaining slow-release fertilizer as described in claim 1, characterized in that, In step S3 of the fertilizer preparation method, the instrument used for coating is a rotary drum coating machine. The fan temperature of the rotary drum coating machine is 50~100 ℃, and the drum speed is 20~60 r / min.

8. The coated water-retaining slow-release fertilizer as described in claim 7, characterized in that, In step S3 of the fertilizer preparation method, the radius of the fertilizer core particles is ≥0.2 cm and the preheating time is ≥5 min; the drying time of the obtained coated fertilizer particles in the rotary drum coating machine is ≥20 min.

9. The coated water-retaining slow-release fertilizer as described in claim 1, characterized in that, In step S3 of the fertilizer preparation method, the mass ratio of the cactus mucus to the inorganic modified polyvinyl alcohol coating liquid is 10-20%, and the mass ratio of the sum of the cactus mucus and the inorganic modified polyvinyl alcohol coating liquid to the mass of the fertilizer core particles in the prepared coated water-retaining slow-release fertilizer is 2-10%.

Citation Information

Patent Citations

  • PROCESS FOR OBTAINING CACTUS MUCILAGE

    BR102019016504A2

  • Seed-treating compositions

    GB936584A